Isolation and characterization of antibacterial compounds in Combretum apiculatum Sond subsp. apiculatum exell - Eloff, Jacobus Nicolaas (University of Pretoria, 2013)
Dissertation (MSc (Pharmacology))--University of Pretoria, 2006.